Genetic diversity in maintainer lines of hybrid rice (Oryza sativa L.) - Akter, A; Hossain, MK; Hasan, MJ; Biswas, PL; Rahman, MM (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 13-18